2002
DOI: 10.1006/qres.2002.2386
|View full text |Cite
|
Sign up to set email alerts
|

Late-Glacial and Early Holocene Environmental and Climatic Change at Lake Tambichozero, Southeastern Russian Karelia

Abstract: High-resolution lithostratigraphy, mineral magnetic, carbon, pollen, and macrofossil analyses, and accelerator mass spectrometry 14C measurements were performed in the study of a sediment sequence from Lake Tambichozero, southeastern Russian Karelia, to reconstruct late-glacial and early Holocene aquatic and terrestrial environmental changes. The lake formed ca. 14,000 cal yr B.P. and the area around the lake was subsequently colonized by arctic plants, forming patches of pioneer communities surrounded by area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 24 publications
6
34
2
8
Order By: Relevance
“…Betula nana is also commonly mentioned in other studies of late glacial sediments of the region (e.g. Wohlfarth et al 2002) and has been reported to have grown near the ice margin even during the LGM (Binney et al 2009). Salix remains at Solova occurred in small quantities; however, willows (probably of shrub growth forms) are not rare in the Estonian late glacial vegetation, as shown by evidence from the Udriku (Amon & Saarse 2010) and Nakri ) localities.…”
Section: Reconstruction Of Terrestrial Vegetation Cover In Southeastementioning
confidence: 84%
See 1 more Smart Citation
“…Betula nana is also commonly mentioned in other studies of late glacial sediments of the region (e.g. Wohlfarth et al 2002) and has been reported to have grown near the ice margin even during the LGM (Binney et al 2009). Salix remains at Solova occurred in small quantities; however, willows (probably of shrub growth forms) are not rare in the Estonian late glacial vegetation, as shown by evidence from the Udriku (Amon & Saarse 2010) and Nakri ) localities.…”
Section: Reconstruction Of Terrestrial Vegetation Cover In Southeastementioning
confidence: 84%
“…In the eastern Baltic area nunatak refugia are hard to imagine and spruce as a continental species (Giesecke et al 2008) most probably overglaciated somewhere in Belarus (Giesecke & Bennett 2004). East of Estonia, in Karelia, conifers were indicated by pollen only in the Preboreal period (Wohlfarth et al 2002). Neither at Solova nor at Nakri the macrofossil assemblages (L. Amon et al, unpublished data) did contain conifer remains; even tree-birch remains were scarce, suggesting a rather distinct late glacial forest line somewhere in northern Latvia.…”
Section: Reconstruction Of Terrestrial Vegetation Cover In Southeastementioning
confidence: 99%
“…An independent reconstruction based on insect fauna composition (Chironomidae) indicates that the July temperature in south-western Norway near the south-western border of the Scandinavian ice sheet (Velle et al 2005) was 5-6°C compared to 11°C at present. In south-eastern Karelia east of the Onega Lake (beyond the limits of the Baltic Sea basin), the minimum July temperature in the Younger Dryas has been estimated at 4°C by pollen and macrofossils of B. nana versus a modern July temperature of 14°C (Wohlfarth 1996;Wastegård et al 2002;Wohlfarth et al 2002Wohlfarth et al , 2007. Mörner (1980) was the first to quantitatively estimate air temperature changes at the Younger Dryas/Holocene boundary by oxygen isotope analysis of lake carbonates from southern Sweden.…”
Section: Climate At the Boundary Of The Younger Dryas/holocenementioning
confidence: 99%
“…The sub-arctic flora arrived in the region at the beginning of the Allerød period (Baranovskaya et al 1977;Wohlfarth et al 2002Wohlfarth et al , 2004, while buried glacier ice was melting causing inversion of the landscape, as was also the case in the area northeast of the Arkhangelsk district which was covered by an older Weichselian ice sheet from the BarentsÁKara Seas (Tveranger et al 1995). From the eastern North Sea across the southern Baltic to northwest Russia, Late Weichselian streamlined terrains separated by belts of terminal moraines possibly generated by narrow and rapidly flowing ice lobes are overprinted by landforms that relate to aerial downwasting (cf.…”
Section: Decay Of the Ice Sheetmentioning
confidence: 99%
“…The age of the oldest organic remnants in sediments from lakes across the downwasting zone belongs to the Allerød interstadial (Ekman & Iljin 1995;Davydova et al 1998). Deposition of organic debris in small lakes on the watersheds covered by dead ice began as late as the Preboreal and Boreal Wohlfarth et al 2002Wohlfarth et al , 2004. Huge areas in the peripheral parts of the SIS therefore stagnated rapidly, fields of debris-covered dead ice spent 4Á7 kyr of degradation as the climate was cold and permafrost still prevailed and because thick overburden retarded heat transfer, thereby delaying downwasting.…”
Section: Decay Of the Ice Sheetmentioning
confidence: 99%